BASIC REQUIREMENTS FOR THE DEVELOPMENT OF TOURISM INBULGARIA - Stanev, Georgi (E-Journal VFU, 2024)
: Serving tourists who have visited various destinations on the territory of thecountry requires the efforts and professional attitude of many specialists in the field. Touristsvisit not only places of accommodation and food, but also other tourist sites.The adoption of functioning regulations is among the priorities of many stateinstitutions. Their activity and the subsequent effectiveness of the decisions are essential for thequality provision of the tourist service and satisfying the wishes of the customers. In this regard,this material draws attention to the main regulatory requirements regarding leading state bodiesthat are relevant at the national and territorial level for the development of tourism.
Keywords: tourism; Ministry of Tourism; organization for the management of the tourist area